Predictably Irrational Hiring. Issue 2 (April 2021) - Machado, Noel G.; Samuel, Jerrin
The hiring process plays a key role in organisational performance, but it involves contentious judgements and decisions. Behavioural economics can help us improve hiring effectiveness and enable the development of strong cultures and successful organisations. Using three historical cases from a Big-Five accounting firm, we present counter-intuitive hiring strategies that are relevant to organisations today. The cases involve six practices related to hiring and nine scientific concepts. The practices are: reverse interview, reverse recruitment, assessment centre (AC) design, structured interviewing, salary history ban, and withdrawal and rationalisation of designations. The scientific concepts are: representativeness heuristic, anticipatory socialisation, affect heuristic, distinction bias, social facilitation (observer effect), dual-process thinking, identity economics, anchoring effect (reference dependence) and social preference (inequity aversion). Finally, we examine the relevance of these practices and concepts as they relate to four human resources (HR) functions: (a) recruitment; (b) selection; (c) compensation and rewards; and (d) culture building.